2012
DOI: 10.1186/2191-1991-2-14
|View full text |Cite
|
Sign up to set email alerts
|

Wealth and antenatal care use: implications for maternal health care utilisation in Ghana

Abstract: The study investigates the effect of wealth on maternal health care utilization in Ghana via its effect on Antenatal care use. Antenatal care serves as the initial point of contact of expectant mothers to maternal health care providers before delivery. The study is pivoted on the introduction of the free maternal health care policy in April 2005 in Ghana with the aim of reducing the financial barrier to the use of maternal health care services, to help reduce the high rate of maternal deaths. Prior to the intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

45
177
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(224 citation statements)
references
References 13 publications
45
177
1
1
Order By: Relevance
“…However, we found that they were more likely to have attended ANC at least four times if they had enrolled in the health insurance scheme. Consistent with those of earlier studies [4,36,42–49], the findings of the current study demonstrated the importance of health insurance in seeking and receiving healthcare. Implementation of the Ghanaian government policy for free medical care for pregnant women under the NHIS could have been a factor in increasing ANC attendance.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, we found that they were more likely to have attended ANC at least four times if they had enrolled in the health insurance scheme. Consistent with those of earlier studies [4,36,42–49], the findings of the current study demonstrated the importance of health insurance in seeking and receiving healthcare. Implementation of the Ghanaian government policy for free medical care for pregnant women under the NHIS could have been a factor in increasing ANC attendance.…”
Section: Discussionsupporting
confidence: 92%
“…The World Health Organization has advised pregnant women to attend ANC at least four times [3]. Appropriate use of ANC could significantly improve early identification and mitigation of risk factors in pregnancy [4]. In contrast, failure to attend ANC or inadequate ANC attendance could lead to complications, exacerbate pre-existing conditions, or worsen the consequences of an unhealthy lifestyle during pregnancy [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The effect was more significant among women with at least secondary school education. The data is consistent with studies from Ghana (Arthur, 2012), migrants in Western (Boerleider, et al, 2013), Brazil (Coimbra et al, 2007), Nigeria (Iyaniwura and Yussuf, 2009), Nepal (Joshi et al, 2014), Ethiopia (Tekelab and Berhanu, 2014). Thus, improving the education of mothers will contribute greatly to the use of maternal and prenatal services by women and thus help in reducing maternal and child mortality.…”
Section: Discussionsupporting
confidence: 77%
“…Despite maternal and child friendly center campaigns, and the expansion of Communitybased Health Planning and Services (CHPS), many births remain unattended by skilled professional care. Many broader social determinants of health care are found to have a great impact on women maternity care utilization in poor settings (Arthur, 2012;Gayawan, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The need for a review of the development of contextspecific measures is highlighted and advocated in this research question of the dissertation. Stakeholders' views in Ghana on maternity care shortcomings cites poor obstetric care, informal payments, poor allocation of skilled providers and unfriendly health provider attitude as factors impeding service provision and utilization (Arthur, 2012;Atinga & Baku, 2013; Josephine Borghi et al, 2003;Perkins et al, 2009). Evidence from other studies show many barriers for maternity care seeking, which are related to providers, health system features and user characteristics (Addai, 1998;Asamoah et al, 2014;Atinga & Baku, 2013;Atunah-Jay et al, 2013; Josephine Borghi et al, 2003;Filippi et al, 2006;Ganle, 2014;Ganle et al, 2015;Lambon-Quayefio & Owoo, 2014;Perkins et al, 2009; Sophie Witter et al, 2007).…”
mentioning
confidence: 99%